Evaluation of Modified Look-Locker Inversion Recovery and Arrhythmia-Insensitive Rapid Cardiac T1 Mapping Pulse Sequences in Cardiomyopathy Patients. Issue 5 (September 2018) - Robison, Sean; Hong, KyungPyo; Kim, Daniel; Lloyd, Rachel; Ramchand, Jay; Hornsey, Emma; Srivastava, Piyush; Smith, Gerard; Kearney, Leighton; Lim, Ruth
Abstract : Objective: The aim of this study was to compare the performance of arrhythmia-insensitive rapid (AIR) and modified Look-Locker inversion recovery (MOLLI) T1 mapping in patients with cardiomyopathies. Methods: In 58 patients referred for clinical cardiac magnetic resonance imaging at 1.5 T, we compared MOLLI and AIR native and postcontrast T1 measurements. Two readers independently analyzed myocardial and blood T1 values. Agreement between techniques, interreader agreement per technique, and intrascan agreement per technique were evaluated. Results: The MOLLI and AIR T1 values were strongly correlated ( r 2 = 0.98); however, statistically significantly different T1 values were derived (bias 80 milliseconds, pooled data, P < 0.01). Both techniques demonstrated high repeatability (MOLLI, r 2 = 1.00 and coefficient of repeatability [CR] = 72 milliseconds; AIR, r 2 = 0.99 and CR = 184.2 milliseconds) and produced high interreader agreement (MOLLI, r 2 = 1.00 and CR = 51.7 milliseconds; AIR, r 2 = 0.99 and CR = 183.5 milliseconds). Conclusions: Arrhythmia-insensitive rapid and MOLLI sequences produced significantly different T1 values in a diverse patient cohort.